A facile deoxyuridine/biotin-modified molecular beacon for simultaneous detection of proteins and nucleic acids via a label-free and background-eliminated fluorescence assay. Issue 18 (7th August 2019) - Yin, Fei; Liu, Liqi; Sun, Xia; Hou, Laiyong; Lu, Yu; Xue, Qingwang; Lin, Tong; Li, Xia; Li, Chen-zhong
Abstract : Simultaneous detection of different types of cancer biomarkers (nucleic acids and proteins) could facilitate early diagnosis of cancer and clinical treatment. Abstract : Simultaneous detection of different types of cancer biomarkers (nucleic acids and proteins) could facilitate early diagnosis of cancer and clinical treatment. Herein, a simultaneous detection platform of proteins and nucleic acids has been developed using a single substrate probe combining a label-free and background-eliminated fluorescence assay. Telomerase and telomerase RNA (TR) were chosen as the models. The molecular beacon (dU-BIO-HP) that contains deoxyuridine/biotin in its side arm, a TR recognition sequence in the loop and a telomerase substrate primer at the stem end was ingeniously designed. In the presence of telomerase, the stem of dU-BIO-HP is elongated by the addition of telomere repeats complementary to the assistant DNA. Furthermore, the formed dsDNA performed as engaging primers to initiate a SDA reaction, generating abundant G-quadruplex monomers. Similarly, on TR, the hybridization between TR and dU-BIO-HP can open its stem, triggering another SDA reaction, producing abundant short ssDNAs. With the G-quadruplex binding with ZnPPIX and ssDNA binding with SG for specific fluorescence responses, the label-free multiple detection can be achieved. In our strategy, the deoxyuridine of dU-BIO-HP acts as a barrier to block the DNA extension due to its strong inhibitory effects on DNA polymerase activity and to make sure that the two SDA reactions occurred independently. The biotin of dU-BIO-HP enables the reduction of the background from the binding between SG, ZnPPIX and dU-BIO-HP through streptavidin–biotin interaction. This method showed an excellent sensitivity with telomerase and TR detection limit of 2.18 HeLa cells per mL and 0.16 × 10 −12 M, respectively. Furthermore, the telomerase and TR in different cell lines have been evaluated as powerful tools for biomedical research and clinical diagnosis.